Πιλοτική εφαρμογή αυτόνομων συστημάτων πλοήγησης για την παραγωγή υψηλής ανάλυσης ορθοφωτογραφιών γεωργικών εκτάσεων - Παπαγεωργίου, Έλενα (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This diploma thesis presents the three-dimensional representation of agricultural land using unmanned aerial vehicles (UAV). Their further data processing method is described using Agisoft Photoscan software and DroneDeploy's online application in order to generate orthophoto of the study area. In the first chapter some general information about the unmanned aerial vehicles are displayed followed by a historical review. Next their use in the agriculture sector is presented giving some example uses as well. Furthermore some main types of UAV are described and analyzed based on their characteristics. The Phantom 3 Pro and Phantom 4 of the DJI UAV series are also described. In the second chapter of the project the study area is presented which concerns an agricultural area of about 9 hectares in the Maroni Village in Cyprus. Next the field data measurements, the aerial mapping procedure using two different UAV in different flight heights and the measurement of the ground control points (GCPs) using GPS are described. In the third chapter the procedure of the data collected from the two UAV are presented. The desktop Agisoft Photoscan software and the DroneDeploy application are used. Then, the final products of the agricultural study area such as point clouds, ground elevation models and orthophotos are presented by the two methods used. Furthermore, the accuracy of the final orthophoto produced from the two flights is evaluated and the results are compared. In the final chapters an overall assessment of the aerial mapping of the agricultural study area and the processing methods used is presented giving some interesting final conclusions and observations.
Keywords: UAV; Orthophoto; Agisoft Photoscan; DroneDeploy; Αgriculture; Ορθοφωτοχάρτης; Γεωργία